PERANCANGAN MEDIA EDUKASI POP-UP BOOK “SI BUJANG: ASAL MULA BURUNG PUNAI” CERITA RAKYAT PELALAWAN PROVINSI RIAU - YUDHA RAHMANTO, Drs. Syafwan, M.Si., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Pop-up books are usually presented with the purpose of providingeducation to children in the form of children's stories, such as fairy tales or inIndonesia itself called folklore or stories that come from the community. Ingeneral, folklore in Indonesia is full of educational elements. One is the story ofthe people of Si Bujang: Asal Mula Burung Punai originating from the Pelalawanarea, Riau Province which tells of a boy named Bujang who is rebellious to hisparents, so Bujang is cursed into a bird of punai. The purpose of this folkloredesign in the media pop-up book in addition to mepopulerkan and turn alsoprovide education to the target audience about the moral upgrading of folklore Si Bujang: Asal Mula Burung Punai this through SWOT analysis method.This design will later generate the visualization of the story of SiBujang: Asal Mula Burung Punai because it is supported by illustrations andvisualization of three dimensions that are expected to increase reading interest for children, contributing in the scientific of Visual Communication Design and can popularize and preserve the tradition story of Pelalawan .The media battle of pop-up book Pelalawan's folklore as the main media,this design is supported by several other media such as: x-banner, poster, t-shirt, sticker, poster, pin, totebag, puzzle, and bottle drink that acts as main media supporter as well as a media campaign.Keywords: Media, pop-ups, books Children's stories, folklore, Si Bujang: AsalMula Burung Punai